Troubleshooting Oracle performance - Antognini, Christian (Expert's voice in Oracle., 2008)
"Troubleshooting Oracle Performance" provides a systematic approach to addressing the underlying causes of poor database application performance. Written for developers by an application developer, this volume gives a systematic approach to solving database application performance problems.